Phenotypic and Molecular Profiling of Pseudomonas aeruginosa Under Thermal Stress Conditions: Profil Fenotipik dan Molekuler Pseudomonas aeruginosa Dalam Kondisi Stres Termal - Wameedh Sabah Shukur (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Pseudomonas aeruginosa is a versatile opportunistic pathogen frequently associated with hospital-acquired infections and notable for its ability to survive under diverse environmental conditions, including elevated temperatures encountered during fever and clinical disinfection procedures. Specific Background: Temperature variation represents a biologically relevant stressor that can alter bacterial physiology, virulence traits, and antimicrobial susceptibility patterns in clinical isolates. Knowledge Gap: Despite its clinical importance, the phenotypic and molecular responses of P. aeruginosa to thermal stress, particularly the integration of phenotypic assays with transcriptomic analysis, remain insufficiently characterized. Aims: This study investigated phenotypic alterations, antibiotic susceptibility modulation, and transcriptomic responses of clinical P. aeruginosa isolates exposed to thermal stress conditions. Results: Exposure to elevated temperatures produced measurable phenotypic changes, including modified growth rates, colony morphology, motility behavior, and biofilm dynamics, accompanied by shifts in antimicrobial susceptibility profiles and transcriptional reprogramming involving heat-shock proteins, stress-response regulators, virulence factors, and resistance-associated pathways. Novelty: The integration of phenotypic characterization with RNA sequencing provides a comprehensive molecular framework for understanding temperature-dependent adaptation in P. aeruginosa. Implications: These findings highlight temperature variation as a critical environmental signal shaping bacterial survival, virulence potential, and antimicrobial response, providing insights relevant to infection control strategies and clinical management of P. aeruginosa infections. Highlights: • Thermal exposure modifies bacterial growth patterns, colony structure, and biofilm dynamics.• Elevated temperature conditions coincide with antimicrobial susceptibility modulation and stress-response activation.• Integrated phenotypic assays and transcriptomic profiling reveal coordinated adaptive mechanisms. Keywords: Pseudomonas Aeruginosa; Thermal Stress; Phenotypic Adaptation; Antibiotic Susceptibility; RNA Sequencing